Fuel Cells and Hydrogen Storage: Challenges Facing Vehicle Manufacturers - Bilal SOLTANI; Nedjem Eddine Benchouia (3èmeCongrès International sur les Energies Renouvelables et le Développement Durable (ERDD-2019), 2019)
The main challenge of our time is to find renewable energy sources that meet the needs of society. Nevertheless, energy must meet several criteria such as abundance, ease and speed of use, but also the cost of production which must be low. In addition, the aspect of "clean and renewable energy" is also to be taken seriously. Today, fuel cells are a magnet for researchers because they have many advantages. First of all, these batteries have the capacity to produce a significant amount of electricity, water and heat. In addition, the reagents of the battery are the oxygen naturally present in the atmosphere and the di-hydrogen that needs to be produced. Its production is therefore a major stake for the installation of the fuel cell. Many hopes rest on the fuel cell. As we have seen, it is one of the energy sources that have the most to become and application areas. With a relatively high efficiency, zero pollutant emissions, this fuel cell has many other advantages such as the variety of batteries that can be adapted to all current needs such as transportation, global electricity generation or digital. Because of the benefits that flow from its use as an automobile fuel, hydrogen is expected to take precedence over other synthetic fuels in the not-too-distant future.